Balagah sebagai Teori Kritik Sastra Arab Formalis: Obyek Bahasan, Praktik, dan Plus- Minusnya - Kamil, Sukron (Buletin Al-Turas, 2011)
The theory of modern litery criticism in the West begins with the birth of the theory of formalism in Russia between 1915-1930 developed by Jacobson, shklovsky, Eichenbaum and others. This theory is the foundation stone of modern literary science that formally consider literary work as art of language and sparate the literary works from other social sciences such as psychology, history, and culture. From this formalism theory then was born the theory of structuralism and its various manifold (post-structuralism), such as semiotics, geneticstructuralism, and others. Based on the formalism theory, literary works as autonomous works must be researched in terms of the work itself (intrinsic elemennts), not from outside ( extrinsic elements), because theory more emphasizes on the beauty of literary works. Therefore, what, is needed in criticizing a literary works is close reading, a microscopic reading of literary works as art of language.